2019
DOI: 10.1371/journal.pcbi.1007334
|View full text |Cite
|
Sign up to set email alerts
|

Learning the structure of the world: The adaptive nature of state-space and action representations in multi-stage decision-making

Abstract: State-space and action representations form the building blocks of decision-making processes in the brain; states map external cues to the current situation of the agent whereas actions provide the set of motor commands from which the agent can choose to achieve specific goals. Although these factors differ across environments, it is currently unknown whether or how accurately state and action representations are acquired by the agent because previous experiments have typically provided this information a prio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Panels (A-D,G,H) are taken directly from Balleine (2013, 2019). Panels (E,F) are redrawn from Dezfouli and Balleine (2019).…”
Section: Humanmentioning
confidence: 99%
“…Panels (A-D,G,H) are taken directly from Balleine (2013, 2019). Panels (E,F) are redrawn from Dezfouli and Balleine (2019).…”
Section: Humanmentioning
confidence: 99%
“…In light of these issues, alternative computational architectures have been proposed [for a review of other taxonomies, see 16] that might better align with classical behavioral findings across species. Furthermore, the recent back-translation of the two-step task for rodents [33][34][35][36][37] could also shed light on these issues. Indeed, translation of models and methodologies between preclinical and clinical research is crucial in the study of basic learning mechanisms in AUD.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This task has been recently back-translated to animal research, showing a similar behavioral pattern in rodents [33][34][35]. Moreover, a recent study has shown that rodents initially only use outcomes to drive behavior, but recover the structure of the environment over the course of learning and also use it to make decisions [36]. Indeed, some studies suggest that both rodents and humans can display predominantly model-based behavior following overtraining in the two-step task [37,38].…”
Section: Behavioral Paradigms and Neural Circuitrymentioning
confidence: 98%
“…Many applications of neuroevolution focus on evolving the connection weights of ANNs [5,9,13,33], however, more complex approaches that evolve both the weights and topologies of ANNs exist [39,46]. Learning complex, sequential or multi-stage tasks is often hard for these neural controllers, as complete information about the environment-including the available actions, their cues, and their consequences-is not usually accessible [12,32]; this is also evident when environments are shared, as the actions of individuals change the context of the environment for others [5]. In nature, behavioural plasticity can be achieved with neuromodulation-a biological process whereby chemical signals are regulated (often also termed "modulated" or "gated") in the brain depending on environmental stimuli [1].…”
Section: Introductionmentioning
confidence: 99%
“…ANNs are just one example of an agent controller in which behaviour can be learned; we use ANNs in line with previous River Crossing testbeds [5,9,33] to explore how ANNs make decisions in social environments to solve tasks of variable complexity. Here, we define a multi-stage task as one that an agent must learn, and pass, through multiple states, and perform different behaviours in different contexts to achieve their goal; this definition is inspired by Reference [12].…”
Section: Introductionmentioning
confidence: 99%